The influence of parental attention and interest in learning on student social studies learning achievement in Elementary School - Iklimatunnajah (CV. Akademi Merdeka, 2024)
This research uses the ex post facto correlation method to examine the relationship between parental attention, interest learning social studies, and student learning outcomes at SDN 1 Pabuaran Wetan. The sample consists of 40 grade IV students selected through stratified random sampling. Data on parental attention, interest learning, and student learning outcomes were collected simultaneously using scales and assessments. Inferential statistical techniques, such as t-tests or ANOVA, will be applied to analyze the data. The research aims to determine if there is a significant relationship between the variables and provide insights into student achievement. The findings will inform the development of effective educational strategies to enhance student interest and improve learning outcomes in social studies. Understanding parental attention and interest learning can contribute to the design of interventions and programs that promote student engagement and academic performance in social studies education.